2014
DOI: 10.1103/physrevc.89.024313
|View full text |Cite
|
Sign up to set email alerts
|

Multi-shell effective interactions

Abstract: Background: Effective interactions, either derived from microscopic theories or based on fitting selected properties of nuclei in specific mass regions, are widely used inputs to shell-model studies of nuclei. The commonly used unperturbed basis functions are given by the harmonic oscillator. Until recently, most shell-model calculations have been confined to a single oscillator shell like the sd shell or the pf shell. Recent interest in nuclei away from the stability line requires, however, larger shell-model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
124
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 34 publications
3
124
0
1
Order By: Relevance
“…The calculated potential-energy surfaces in Ref. [13] also indicate the likelihood of shape coexistence in 70 Ni.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculated potential-energy surfaces in Ref. [13] also indicate the likelihood of shape coexistence in 70 Ni.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this effort has been concentrated thus far on 68 Ni itself, with substantial improvements made to the level scheme [30][31][32] and deduced decay rates [12,31], as well as with comparisons of the data with Monte-Carlo shellmodel (MCSM) calculations [33,34]. The latter have provided strong evidence for coexisting spherical, oblate, and prolate shapes in this nucleus [12,13]. The calculated potential-energy surfaces in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such context, nuclei at Z=28, N=50 shell gaps are particularly interesting since they are good candidates to reveal changes into the shell structure. Recent shell model calculations showed that these modifications not only affect the level sequence but also the overall shape of the nucleus [2]. Both central and non-central components (i.e.…”
Section: Introductionmentioning
confidence: 99%